2022
DOI: 10.1371/journal.pgph.0000599
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of microvascular and macrovascular complications of diabetes in newly diagnosed type 2 diabetes in low-and-middle-income countries: A systematic review and meta-analysis

Abstract: There is an excessive burden of diabetes complications in low-resource settings. We conducted a systematic review to determine the nature and frequency of diabetes complications in newly diagnosed with type 2 diabetes. A systematic search was performed using Medline, CINAHL and Global Health online databases from inception to July 2020. Articles reporting prevalence of microvascular or macrovascular complications within six months of type 2 diabetes diagnosis and published in English or French from low- and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Long-term hyperglycemia can damage the cardiovascular system, resulting in vascular complications of diabetes (VCD) (i.e., microvascular complications and macrovascular complications). 3 Microvascular complications mainly include diabetic nephropathy (DN) and diabetic retinopathy (DR), 6,7 whereas macrovascular complications mainly include diabetic cardiomyopathy (DCM). A cross-sectional study reported that 12% of diabetic patients suffered from DR, 15% suffered from DN, and the median prevalence of macrovascular complications was lower than that of microvascular complications (about 10%).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Long-term hyperglycemia can damage the cardiovascular system, resulting in vascular complications of diabetes (VCD) (i.e., microvascular complications and macrovascular complications). 3 Microvascular complications mainly include diabetic nephropathy (DN) and diabetic retinopathy (DR), 6,7 whereas macrovascular complications mainly include diabetic cardiomyopathy (DCM). A cross-sectional study reported that 12% of diabetic patients suffered from DR, 15% suffered from DN, and the median prevalence of macrovascular complications was lower than that of microvascular complications (about 10%).…”
Section: Introductionmentioning
confidence: 99%
“…However, the disability rate and case fatality rate of macrovascular complications were higher. 7 The potential molecular mechanisms of VDC include inflammation, inappropriate activation of oxidative stress, mitochondrial dysfunction, dyslipidemia, and thrombosis, which together promote metabolic disorder and further promote VCD. 8 Recent evidence has revealed that the abnormal release of extracellular vesicles and their carried noncoding RNAs (ncRNAs) also contribute to the development of VCD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The burden caused by the multiple complications of DM on families and society has become increasingly serious. [1] Notably, the prevalence of T2DM in China is particularly high. A study has projected that by the year 2050, the age-standardized prevalence of DM worldwide would increase by > 2%.…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 diabetes (T2D) is a worldwide concern that establishes a significant influence on patient mortality and morbidity [ 1 ], affecting about 463 million adult people aged 20–79 years [ 2 ], which is expected to increase by 51% to 700 million by 2045 [ 2 , 3 ]. T2D is characterized by peripheral insulin resistance [ 4 , 5 ], which diminishes glucose reuptake in skeletal muscle and adipose tissue, leads to defective hepatic glucose output, and impairs insulin production from pancreatic B-cells [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%